Mesh resolution consideration for the viability prediction of lost salt cores in the high pressure die casting process. (1st January 2014) - Fuchs, B.; Körner, C.
High pressure die casting is limited in its geometry since a lost core technology as with sand or low pressure casting is not state-of-the art. Using lost cores made from sodium chloride may be a solution for high pressure die casting. Due to the high dynamical forces during the casting process, core failure is still a problem, especially for high ingate velocities. In this contribution the possibilities of numerical simulation are investigated to predict core failure during the casting process. Numerical results are created with different mesh resolutions and compared to evaluate the simulation results with according mechanical characterisation. In this way an objective approach to find process parameters based on the mechanical properties of the salt cores without costly and time consuming trial-and-error-testing could be established. Furthermore, a critical mesh resolution could be determined.